Usaha Mikro Kecil dan Menengah (UMKM) Berkelanjutan melalui Literasi Keuangan - Markonah, Markonah; Riwayati, Hedwigis Esti; Jinan, Achmad Syauqi Ilal; Terada, Yoshitaka (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
MSMEs play an important role in the global and local economy, contributing to job creation, innovation and economic growth. However, many MSMEs face financial challenges that can hinder their development. This is why financial literacy is the key to empowering MSMEs to be sustainable. Micro, Small and Medium Enterprises (MSMEs) are the most strategic sector of the national economy and concern the livelihoods of many people, making them the backbone of the national economy. This research uses qualitative research methods, data collection is carried out using questionnaires, observation and documentation methods. Data analysis techniques use percentages as a basis for interpretation and description to produce research results. MSME players must develop modern business models. The government is also encouraging MSME players to develop modern business models, by building digital technology as a platform in the process of sustaining MSME activities. Strengthening digital technology to support MSME economic activities. In the sustainability strategy, digital technology must be the main platform in MSME business processes. Where, in the future it is hoped that MSMEs can use digital technology to implement financial literacy.